A Methodology for the Historiography of Ancient Religion - Rüpke, Jörg (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2021)
Starting from a discussion about the usefulness of a historical approach to ancient religion, I propose basing the historiography of ancient religion on a set of three concepts, replacing three others that have been widely used. First, I contend that we need to shift our focus from questions of identity to questions of agency, not least in the face of earlier traditions of historiography of regions outside the imperial capitals. The application of an agentic perspective entails a further unavoidable consequence. The concept of “religions” must be replaced by that of “lived religion”, even for the past, once again shifting the focus to the local and the entire range of social agents and their cultural production. This agentic and material focus is further supplemented by a spatial one. Thus, I propose moving away from the widespread focus on civic religion in cities to embrace the perspective of urban religion. Lastly, I briefly touch upon the problem of the selection of forms of contemporary historiography of religion.